A grating coating sensor for quantitative monitoring of metal structure cracks under varying ambient temperature. (31st March 2022) - Song, Yujian; Liu, Xinbo; Zhang, Deyue; Fan, Xianghong; Cui, Ronghong; Zheng, Yan; Wang, Ye
Highlights: A grating coating sensor was a health monitoring method of aircraft metal structure based on potential method, which was attractive for quantitative crack monitoring. A grating coating sensor was prepared by physical vapor deposition technology, and the crack quantitative monitoring ability of the sensor was verified by simulation and experiment. A temperature compensation method for grating coating sensors was proposed. The temperature compensation ability of the optimized sensor was verified by experiments. Abstract: The metal structure hole edge is the most likely location for cracks in the aircraft structure. Quantitative monitoring of the of metal structure hole edge is an important research content in the field of structural health monitoring (SHM). This paper proposed a grating coating sensor for quantitatively monitoring structural cracks based on the electric potential method. First, the structural composition and working principle of the grating coating sensor were introduced. A grating coating sensor was prepared by arc ion plating technology, and the coating sensors ability to quantitatively monitor cracks was verified by fatigue crack monitoring experiment. Then, the influence mechanism of ambient temperature change on the output signal of coating sensors was analyzed and verified by experiments. Moreover, a temperature compensation technology was developed. Based on the grating coating sensor, an optimized sensor with a temperature compensation channel was proposed, and define the output signal, SC, of the optimized sensor. Finally, the fatigue crack monitoring experiment under varying ambient temperature was carried out. The results show that optimized grating coating sensors can quantitatively monitor fatigue cracks under varying ambient temperature. The research results also have great reference value for other sensors based on the electric potential method.